DEVELOPMENT OF JOINT CHEMICAL, BIOLOGICAL, RADIOLOGICAL AND NUCLEAR (CBRN) RESPONSE CAPABILITY IN SOUTH ASIA: CURRENT STATUS & FUTURE PROSPECTS - Saman Choudary; Muhammad Usman Asghar (Margalla Papers, 2025)
Protection against the consequences and impacts of Chemical, Biological, Radiological, and Nuclear (CBRN) events remains a top concern in the national and international security framework of nation-states around the globe. The growing threats in the CBRN domain warrant attention to enhance capabilities for an effective CBRN response. The South Asian region requires even more comprehensive and integrated efforts to establish a mechanism for addressing these threats, given the region's complex geostrategic and security dynamics. The area lacks a well-developed coordination mechanism for sharing information and addressing cross-border contamination scenarios in the event of a CBRN incident. This paper aims to explore potential areas of cooperation, integration, and coordinated action among South Asian states at the regional level. A doable framework is proposed to develop joint regional capabilities for prevention, improved preparedness, and incident response strategies. It will focus on integrating the communication mechanism between the regulatory institutions of the participating states. It is emphasized that cooperation among states is crucial for practical accident assessments and the coherence of responses, which are essential for preventing CBRN events. It will help ensure the unified implementation of protective action plans, independent of national border lines, to effectively respond to CBRN incidents that could have critical regional and international implications.